Effect of drought on photosynthesis, growth, and light interception in dry beans. - Nuñez-Barrios, Abelardo (2016)
The effect of water deficit on leaf area index, light interception, stomatal conductance, and dry matter production in dry beans was studied in this investigation carried out at Michigan State University, where drought treatments were imposed at different phenological stages such as vegetative (VS), initial flowering (IF) and seed fiJling (SF). Water stress rapidly reduced the Jeaf area index, mostly in IF, causing a significant decrease in light interception. Stomatal conductance and photosynthesis were also reduced by water deficit. However, the C02 assimilation rate had a significant decrease only when stomatal conductance was lower than 0.8 cm/sec. Dry matter production was cJosely related to light interception. Nevertheless, at the same amount of intercepted radiation, production of dry matter in IF lagged behind the control by 6.5%.